Upskilling of the School Heads in the New Normal - Marco B. Agravante; Gerry S. Digo; Susan S. Janer (East Asian Journal of Multidisciplinary Research, 2023)
This study aimed to upskill the leadership competencies of school heads in Magallanes, Sorsogon, Philippines for the school year 2021–2022. This study employed the mixed-methods sequential explanatory design which outlined the quantitative and qualitative methods using the descriptive-survey method and interview to the purpose of this study. The results of a survey revealed the three highest ranks in terms of upskilling needs of school heads were mentoring and coaching, curriculum development, and management of educational projects. However, the interview transcript reveals that the upskilling for school heads significantly impacted all aspects of leadership development. The leadership training conducted using the upskilling design effectively improves the leadership competencies of school heads.